2022
DOI: 10.1111/1467-8268.12654
|View full text |Cite
|
Sign up to set email alerts
|

The revenue efficiency consequences of the announcement of a tax transition reform: The case of WAEMU countries

Abstract: Does the revenue replacement strategy of border taxes with domestic revenue collection (tax transition) increase efficiency in collecting revenues in developing countries? This article attempted to answer the question, by assessing the efficiency consequences of announcing a tax transition reform program in West African Economic and Monetary Union (WAEMU) countries. Through an impact evaluation framework with propensity score matching and synthetic control method, we find that the announcement of this reform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Using a fixed‐effects panel model with instrumental variables, he finds that multilateral aid affects tax revenues positively while bilateral aid does not. Adandohoin and Gammadigbe (2022) examine the efficiency consequences of announcing a tax transition reform program in the WAEMU. Using propensity score matching and synthetic control method, they find that the announcement of this reform in the WAEMU increases efficiency in mobilising resources at the community level by 4.3% around the reform agenda.…”
Section: Why Do People Pay Tax? a Related Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a fixed‐effects panel model with instrumental variables, he finds that multilateral aid affects tax revenues positively while bilateral aid does not. Adandohoin and Gammadigbe (2022) examine the efficiency consequences of announcing a tax transition reform program in the WAEMU. Using propensity score matching and synthetic control method, they find that the announcement of this reform in the WAEMU increases efficiency in mobilising resources at the community level by 4.3% around the reform agenda.…”
Section: Why Do People Pay Tax? a Related Literature Reviewmentioning
confidence: 99%
“…Firstly, the paper contributes to the literature by providing, for the first time to the best of our knowledge, evidence on the behavioural aspects of tax compliance in the WAEMU. Bayale (2020) and Adandohoin and Gammadigbe (2022) recently examined, respectively, the effect of different types of foreign aid on tax revenue and the efficiency consequences of announcing a tax transition reform program in the WAEMU. Ihuarulam et al (2021) investigate how tax revenue is related to selected macroeconomic variables in West Africa.…”
mentioning
confidence: 99%
“…Many of the studies revealed that technological issues [16] and the unavailability of infrastructure [3], [18] were barriers to the successful use of digitalized systems. Other studies also emphasized an increase in cost and financial constraints as a hindrance to successful digitalization [14], [19]. Other issues are individually based, such as poor attitudes towards digitalization, lack of required ICT skills and technical know-how, and individual characteristics [18].…”
Section: Diffusion Of Innovationmentioning
confidence: 99%
“…The goal of building end-user capacity to use the digital platform effectively and efficiently influenced the meeting of specific normative standard requirements. This was necessary because of the transition from erstwhile systems to the use of an integrated system which is noted in studies as an aid for the use of information systems [3], [18], [19]. Training end-users on the use of the system was a standard requirement which led to the effective use of the system.…”
Section: Proposition Two (P2): Normative Factors Influence the Digita...mentioning
confidence: 99%